(untitled) (Journal of Asian Development Studies, 2025)
There is substantial literature on the cyberbullying activities of young adults associated with problematic social media use; however, studies specifically examining the relationship between Facebook addiction and cyberbullying perpetration—particularly in Pakistan— remain limited. Therefore, the objective of this study is to investigate the relationship between Facebook addiction and cyberbullying perpetration among young Pakistani adults. A quantitative correlational research design and purposive sampling technique were employed to collect data from 244 Pakistani young adults between the ages of 18 and 35 (179 men and 65 women), with a mean age of 23.69 years (SD = 3.56). The study utilized two instruments: the Bergen Social Media Addiction Scale to assess Facebook addiction and the Cyberbullying Perpetration and Victimization Questionnaire (used only to measure cyberbullying perpetration). The results revealed a positive and significant association between Facebook addiction and cyberbullying perpetration among young adults. The study highlights implications for mental health awareness, the promotion of help-seeking behaviors, and improved socialization.